Stochastic lead time demand estimation via Monte Carlo simulation technique in supply chain planning - Mohamad Mahdavi,; Mojtaba Mahdavi, (Universiti Kebangsaan Malaysia, 2014)
This paper considers a Monte Carlo simulation based method for estimating cycle stocks (production lot-sizing stocks) in a typical batch production system, where a variety of products is scheduled for production at determined periods of time. Delivery time is defined as the maximum lead time and pre-assembly processing time of the product’s raw materials in the method. The product’s final assembly cycle and delivery time, which were obtained via the production schedule and supply chain simulation, respectively, were both considered to estimate the demand distribution of product based on total duration. Efficient random variates generators were applied to model the lead time of the supply chain’s stages. In order to support the performance reliability of the proposed method, a real case study is conducted and numerically analyzed.